Synthesis of C2-Symmetric Diphosphormonoamidites and Their Use as Ligands in Rh-Catalyzed Hydroformylation: Relationships Between Activity and Hydrolysis Stability - Luhr-Sierra, S (Wiley-VCH Verlag, 2017)
A series of diphosphoramidites has been synthetized with a piperazine, homopiperazine, and an acyclic 1,2-diamine unit in the backbone. New compounds were tested alongside related N-acyl phosphoramidites as ligands in the Rh-catalyzed hydroformylation of n-octenes to investigate their influence on the activity and regioselectivity. A subsequent study of their hydrolysis stability revealed that the most stable ligands induced the highest activity in the catalytic reaction. © 2016 The Authors. Published by Wiley-VCH Verlag GmbH & Co. KGaA.